Fungsi Echo Sounder Dalam Membantu Olah Gerak Kapal Di Perairan Yang Sempit Dan Dangkal - Winarsih Winarsih; Fitri Suprapti (Jurnal Maritim Polimarin, 2018)
The purpose of this study is to find out the extent of the effect of the echosounder function on ship movements in narrow and shallow waters. In achieving these objectives, research is carried out using the type of analytical description through the drawing of research objects to be analyzed and the development model of the object of research is sought. The sample taken in this study is a passenger ship which is at the Port of Tanjung Emas Semarang. Determination of the sample by means of purposive random sampling, namely researchers have determined directly the object of research, both for ships and for respondents. In the process of collecting data, researchers use several ways to obtain data and information through interviews and questionnaires (questionnaires). The results of the study showed that the echo sounder function affected ship movements in narrow and shallow waters in a significantly positive manner. Positive influence means that the better the echo sounder function that is used will provide good ship motion, especially in narrow and shallow waters. Echo sounders affect ship movement by 49.8%, while the remaining 50.2% is explained by other factors. Another factor in question is the facilities provided by PT. PELNI and its own human resources.